BlackLivesMatter in Healthcare: Racism and Implications for Health Inequity among Aboriginal and Torres Strait Islander Peoples in Australia - Kathomi Gatwiri; Darlene Rotumah; Elizabeth Rix (International Journal of Environmental Research and Public Health, 2021)
Despite decades of evidence showing that institutional and interpersonal racism serve as significant barriers to accessible healthcare for Aboriginal and Torres Strait Islander Peoples, attempts to address this systemic problem still fall short. The social determinants of health are particularly poignant given the socio-political-economic history of invasion, colonisation, and subsequent entrenchment of racialised practices in the Australian healthcare landscape. Embedded within Euro-centric, bio-medical discourses, Western dominated healthcare processes can erase significant cultural and historical contexts and unwittingly reproduce unsafe practices. Put simply, if Black lives matter in healthcare, why do Aboriginal and Torres Strait Islander Peoples die younger and experience ‘epidemic’ levels of chronic diseases as compared to white Australians? To answer this, we utilise critical race perspectives to theorise this gap and to de-center whiteness as the normalised position of ‘doing’ healthcare. We draw on our diverse knowledges through a decolonised approach to promote a theoretical discussion that we contend can inform alternative ways of knowing, being, and doing in healthcare practice in Australia.